THEORETICAL BASES OF MANAGEMENT OF INNOVATIVE DEVELOPMENT OF THE ENTERPRISE OF MECHANICAL ENGINEERING - Y. Vnutchkov; L. Uglova; D. Komonov (Вестник университета)
In the article it is proved that one of methods of strategic management of mechanical engineering of the enterprises in the conditions of the competition to foreign producers is effective functioning of system of financial planning by a production activity. The double-circuit system of financial planning by the enterprise is considered, and also it her basic provisions are formulated. The special attention is paid to a question of information support of financial planning at the enterprise.